2020
DOI: 10.15252/embr.201949807
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic CDK 4 regulates thermogenesis by modulating sympathetic innervation of adipose tissues

Abstract: This study investigated the role of CDK4 in the oxidative metabolism of brown adipose tissue (BAT). BAT from Cdk4−/− mice exhibited fewer lipids and increased mitochondrial volume and expression of canonical thermogenic genes, rendering these mice more resistant to cold exposure. Interestingly, these effects were not BAT cell‐autonomous but rather driven by increased sympathetic innervation. In particular, the ventromedial hypothalamus (VMH) is known to modulate BAT activation via the sympathetic nervous syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that the integrity of VMH neurons is required to maintain the sympathetic activity and outflow to peripheral tissues ( 65 , 66 ). Our data show that OGT deletion in VMH neurons reduces the activity of the sympathetic nervous system both systemically and locally in white adipose tissues ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the integrity of VMH neurons is required to maintain the sympathetic activity and outflow to peripheral tissues ( 65 , 66 ). Our data show that OGT deletion in VMH neurons reduces the activity of the sympathetic nervous system both systemically and locally in white adipose tissues ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the endocannabinoid system in SF-1 neurons was elaborated by knocking out monoacylglycerol hydrolase α/ β-hydrolase domain 6 (ABHD6), which disturbs the endocannabinoid system and impairs thermogenic and cold-enduring ability 208 . Another key regulator, cyclin-dependent kinase 4 (CDK4), also showed importance in the cold-induced adaptive thermogenesis of SF-1 neurons, as the deletion of CDK4 increased cold resistance in mice, with increased sympathetic outflow and UCP1 expression in BAT 209 .…”
Section: Hypothalamic Control Of Cold-induced Thermogenesismentioning
confidence: 99%
“…Many studies have shown that the deletion of various key factors specifically in the SF-1 neurons, such as leptin receptor, ERα, phosphoinositide 3-kinase and AMPK, etc. involved in the regulation of energy homeostasis and obesity [272,[281][282][283][284][285][286]. VMH may be the origin of leptin-mediated sympathoexcitation which contributes to obesity-related hypertension [287], but no cardiovascular effects were reported in these mutant mouse models.…”
Section: Steroidogenic Factor 1 (Sf-1)mentioning
confidence: 99%